ETHNOMATHEMATICAL REVIEW OF LUWUNESE TRADITIONAL VALUES IN SOUTH CELEBES INDONESIA - Nugraha, Yuda Satria; Nessa, Widya (PEOPLE: International Journal of Social Sciences, 2019)
Indonesia is one of the countries with a high level of diversity in the world. It makes Indonesia to be rich of culture and has many traditional values ​​that must be upheld. Traditional values ​​are part of the cultural identity possessed by a society group, not exception for Luwunese, one of the cultural groups in South Celebes Indonesia. The traditional values ​​of Luwunese such as Getteng, Lempu’, Tongeng, and Adele’ are four of fundamental characters that must be preserved and passed on to each next generation. One effort in preserving these aspects of culture is through education. Education is seen as the best effort in inheriting values ​​and culture because it is the preparation process of the younger generation in living life and achieving life goals effectively and efficiently. Both of education and culture cannot be separated, so that every learning in school is expected to be integrated with culture. In mathematics learning, ethno mathematics is one of the learning approaches that links mathematics and local culture. Through this approach, learning mathematics in schools is expected to be able to internalize traditional values ​​that apply in the local society. This research is a qualitative research in the form of a literature study with an ethnographic approach to uncover the traditional value philosophy of the Luwunese and to give some school mathematics topics related to it, such as number, algebraic equation, geometry, sequence, and others. This study aims as a form of effort to preserve traditional values ​​to students and preventive efforts of an opportunities for pluralistic nation disintegration.